Designing intersectional online education : critical teaching and learning practices - Woodley, Xeturah M.; Rice, Mary, 1980- (New York, NY : Routledge, 2022)
"Designing Intersectional Online Education provides expansive yet accessible examples and discussion about the intentional creation of online teaching and learning experiences that critically center identity, social systems, and other important ideas in design and pedagogy. Instructors are increasingly tasked with designing their own online courses, curricula, and activities but lack information to support their attention to the ever-shifting, overlapping contexts and constructs that inform students' positions within knowledge and schooling. This book infuses today's technology-enhanced education environments with practices derived from critical race theory, culturally responsive pedagogy, disability studies, feminist/womanist studies, queer theory, and other essential foundations for humanized and socially just education. Faculty, scholars, technologists, and other experts across higher education, K-12, and teacher training offer fresh, robust insights into how actively engaging with intersectionality can inspire designs for online teaching and learning that are inclusive, intergenerational, anti-oppressive, and emancipatory"--
Critical pedagogy & culturally responsive pedagogy : an introduction / Yvonne El Ashmawi, Elissa West Frazier -- Designing for cultural responsiveness in P20 online learning environments / Elissa West Frazier, Yvonne El Ashmawi -- Interest convergence : higher education fragility, online learning, and critical race theory / Ramona Cutri, Nouf Alsuwaida, Xeturah M. Woodley -- We are one, but we are many : using disabilities studies to inform intersectional education online / Shelley Kinash, Madelaine-Marie Judd -- Womanist and feminist pedagogy : infusing the wisdom of women into online education / Shamika Klassen -- Multiplying the possibilities of knowledge : queering online teaching and learning / Tabitha Parry Collins, Linda E. Oldham -- Using Freirean and Rogerian theory to create anti-racist and peace-based intersectional online learning communities / Jennifer L. Martin, Denise K. Bockmier-Sommers, Martin D. Martsch -- Telecollaboration and critical cultural connections / Patricia S. McClure, Lauren Cifuentes -- Queering online pedagogies in gender & sexuality studies / M. Catherine Jonet, Laura Anh Williams -- Tensions in adapting a mandatory indigenous education course to an online environment / Elisa Lacerda-Vandenborn, Jennifer Markides, Teresa A. Fowler, Aubrey Hanson, Jennifer MacDonald, Yvonne Poitras Pratt, Patricia Danyluk -- An autoethnographic rhapsody of learning to teach diverse K-12 students online / Mark Stevens -- Teaching writing informed by systemic functional linguistics : bringing professional development up to scale through online courses / Maria Estela Brisk, Tracy Hodgson-Drysdale, Elizabeth MacDonald.
Keywords: Web-based instruction -- Design; Web-based instruction -- Social aspects; Critical pedagogy; Culturally relevant pedagogy; Interdisciplinary approach in education; EDUCATION / Distance Education & Learning; EDUCATION / Multicultural Education